PENGARUH KEPUTUSAN INVESTASI, KEBIJAKAN DIVIDEN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Rieke Diah Delarosa Sarmin; Sri Hasnawati; Ahmad Faisol (Faculty of Economics and Business University of Lampung, 2021)
The decisions that managers in a company will take will affect firm value in their company. This decision consists of investment decisions, financing decisions, and dividend policy. The firm value determined not only the decisions taken but also the amount of profit earned. This research aimed to examine the effect of investment decisions, financing decisions, and dividend policy on firm value. The secondary data in this research was obtained from the official website of the Indonesia Stock Exchange. By using the purposive sampling method, the sample selected was 11 manufacturing companies listed in the LQ45 index. The analysis technique used in this study were descriptive statistics and multiple linear regressions. The error rate used is 5%. The finding shows that investment decisions and profitability positively affect firm value, while dividend policy does not.